2015
DOI: 10.1175/jcli-d-14-00112.1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Seasonal Prediction of Temperature and Precipitation over Land in a High-Resolution GFDL Climate Model

Abstract: This study demonstrates skillful seasonal prediction of 2-m air temperature and precipitation over land in a new high-resolution climate model developed by the Geophysical Fluid Dynamics Laboratory and explores the possible sources of the skill. The authors employ a statistical optimization approach to identify the most predictable components of seasonal mean temperature and precipitation over land and demonstrate the predictive skill of these components. First, the improved skill of the high-resolution model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 46 publications
7
138
0
Order By: Relevance
“…This feature is also seen in the satellite-only TRMM 3B43 data set ( , Huffman et al, 2007not shown) and is qualitatively consistent with realistic high-resolution climate models from the Geophysical Fluid Dynamics Laboratory (e.g. GFDL-CM2.5), which show this feature in the western Amazon and all along the eastern tropical Andes (Jia et al, 2015).…”
Section: Rainfall Anomalies Associated With the Equatorial Pacific Sssupporting
confidence: 84%
“…This feature is also seen in the satellite-only TRMM 3B43 data set ( , Huffman et al, 2007not shown) and is qualitatively consistent with realistic high-resolution climate models from the Geophysical Fluid Dynamics Laboratory (e.g. GFDL-CM2.5), which show this feature in the western Amazon and all along the eastern tropical Andes (Jia et al, 2015).…”
Section: Rainfall Anomalies Associated With the Equatorial Pacific Sssupporting
confidence: 84%
“…We assume that the FLOR-FA and HiFLOR modeled responses to changes in radiative forcing are meaningful estimates of the sensitivity of precipitation extremes in the real climate system, since these models capture multiple physical factors affecting precipitation extremes in a physically based and internally consistent framework. This assumption is motivated in part because of the ability of these models to simulate large-scale precipitation and temperature over land (e.g., Van der Wiel et al, 2016;Delworth et al, 2015;Jia et al, 2015Jia et al, , 2016, precipitation extremes over the US (Van der Wiel et al, 2016), modes of climate variability (e.g., Vecchi et al, 2014;Murakami et al, 2015), the meteorological phenomena that led to precipitation extremes and their relationship to modes of climate variability (e.g., Vecchi et al, 2014;Krishnamurthy et al, 2015;Zhang et al, 2015Zhang et al, , 2016Pascale et al, Hydrol. Earth Syst.…”
Section: Crucial Assumptionsmentioning
confidence: 99%
“…We performed a preliminary investigation of the dependence of distance on the effect of anthropogenic forcing and natural variability on TC frequency near Hawaii, which revealed that the dependence is small qualitatively. To assess the ability of FLOR to predict the TCs near Hawaii, we first analyzed a retrospective seasonal forecast made using FLOR initialized on 1 July for each year of 1980-2014 (Vecchi et al 2014;Jia et al 2015; see online supplemental material). Figure 23.2a shows the time series of TC number predicted by FLOR, which reasonably predicts the interannual variations of observed TC frequency (r = 0.59).…”
Section: Acknowledgements: We Thankmentioning
confidence: 99%